Algunas características psicológicas de alumnos con problemas académicos - Salas, Edwin (2000)
Three hundred fifty-seven university records of students reported as undergoing academic problems were studied between Abril 1990 and August 1996. Research was aimed at determining the contributing factors to the problem and also at designing academic support programs and psychopedagogical support actions, and others on a preventive basis. Three study areas were selected: intelligence, as assessed through the WAIS test; personality as assessed through both the Guilford-Zimmerman Temperament and the MMPI Inventories; and study habit, through Brown’s Study Abilities Survey.